Characterization and modeling of three-dimensional self-healing shape memory alloy-reinforced metal-matrix composites. (December 2016) - Zhu, Pingping; Cui, Zhiwei; Kesler, Michael S.; Newman, John A.; Manuel, Michele V.; Wright, M. Clara; Brinson, L. Catherine
Abstract: In this work, three-dimensional metal-matrix composites (MMCs) reinforced by shape memory alloy (SMA) wires are modeled and simulated, by adopting an SMA constitutive model accounting for elastic deformation, phase transformation and plastic behavior. A modeling method to create composites with pre-strained SMA wires is also proposed to improve the self-healing ability. Experimental validation is provided with a composite under three-point bending. This modeling method is applied in a series of finite element simulations to investigate the self-healing effects in pre-cracked composites, especially the role of the SMA reinforcement, the softening property of the matrix, and the effect of pre-strain in the SMA. The results demonstrate that SMA reinforcements provide stronger shape recovery ability than other, non-transforming materials. The softening property of the metallic matrix and the pre-strain in SMA are also beneficial to help crack closure and healing. This modeling approach can serve as an efficient tool to design SMA-reinforced MMCs with optimal self-healing properties that have potential applications in components needing a high level of reliability.